PENGUKURAN TINGKAT KAPABILITAS SISTEM INFORMASI DOKUMEN ELEKTRONIK (SIDOEL) PT ANGKASA PURA II (PERSERO) MENGGUNAKAN COBIT 5.0 DOMAIN DSS DAN MEA - Adetya Rezky Ramadhan (2020)
To improve information services for employees and managerial at PT Angkasa Pura II (Persero). Therefore, special application to support employees ' performance in the creation of a memorandum of service for the benefit of correspondence in the company environment of PT Angkasa Pura II (Persero) in the form of electronic Document Information System (SIDOEL). Therefore, as a form of implementation of the use of information technology in managing data/information as one of the valuable assets of the company then done performance assessment and evaluation of the system and management to be more optimal. The assessment was conducted by COBIT 5 Framework method, researchers focused on performing Capability Level measurement in the process of managing service and incident requests (DSS02) by obtaining 3 at the capability level, managing problems (DSS03) by obtaining 3 at the capability level, managing security Services (DSS05) by gaining 2 at the capability level, manage Business Process Control (DSS06) by gaining 2 at capability level, monitor, evaluate and assess implementation and suitability (MEA01) by getting 2 at capability level, monitor, evaluate and assess system with external control (MEA03) by getting 3 at capability level, while capability level is expected to be level 5 (Optimising Process). In this study, the recommendations aimed at improving the expected process capabilities could achieve the desired level of capability.